2019
DOI: 10.3174/ajnr.a6314
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Study of the Pipeline Embolization Device with Shield Technology in Unruptured Aneurysms (PEDSU)

Abstract: BACKGROUND AND PURPOSE: The recently introduced Pipeline Flex Embolization Device with Shield Technology (Pipeline Shield) is the third generation of Pipeline flow-diverter devices. It has a new stent-surface modification, which reduces thrombogenicity. We aimed to evaluate clinical and radiographic (safety and efficacy) outcomes of the Pipeline Shield. MATERIALS AND METHODS: The 30-day and 1-year mortality and morbidity rates and the 6-and 18-month radiographic aneurysm occlusion outcomesIndicates open access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“… 23 A more recent study in 41 patients with 44 unruptured cerebral aneurysms reported no thromboembolic or hemorrhagic events during procedures, one periprocedural thromboembolic event (2.4%) in a patient who also had atrial fibrillation, and no thromboembolic events during follow-up. 29 In the present study, there were three thromboembolic events during follow-up, resulting in an event rate of 1.5%, consistent with previous reports and much lower than thromboembolic event rates of up to 6.5% reported for previous-generation PEDs. 15 30 Taken together, these findings support low thrombogenicity and improved safety of the PED-Shield relative to its predecessors.…”
Section: Discussionsupporting
confidence: 92%
“… 23 A more recent study in 41 patients with 44 unruptured cerebral aneurysms reported no thromboembolic or hemorrhagic events during procedures, one periprocedural thromboembolic event (2.4%) in a patient who also had atrial fibrillation, and no thromboembolic events during follow-up. 29 In the present study, there were three thromboembolic events during follow-up, resulting in an event rate of 1.5%, consistent with previous reports and much lower than thromboembolic event rates of up to 6.5% reported for previous-generation PEDs. 15 30 Taken together, these findings support low thrombogenicity and improved safety of the PED-Shield relative to its predecessors.…”
Section: Discussionsupporting
confidence: 92%
“…3 Even third-generation FDs with surface modifications with synthetic biocompatible phosphorylcholine seem to have similar outcomes compared with previous generations of FDs. [5][6][7] Noncompliance with dual antiplatelet therapy and resistance to clopidogrel therapy are also known causes of in-stent thrombosis; however, there is controversy regarding the use of platelet function testing prior to FD implantation and converting known nonresponders to other antiplatelet medications such as ticagrelor or prasugrel. 8 Although certainly attention to patient compliance and identifying clopidogrel nonresponders before FD treatment should reduce the incidence of thrombosis formation, we would still have some patients who may have this complication regardless of clopidogrel responsiveness and compliance with medications.…”
Section: Discussionmentioning
confidence: 99%
“…Complete aneurysm occlusion was obtained in 70.8 % at 6-month and 77.2 % at 12-month. In a non-industry-sponsored study (PEDSU = Pipeline Embolization Device with Shield Technology in Unruptured Aneurysms) with DAPT, the cumulative morbidity and mortality at 1-year were slightly higher (6.8 % and 2.3 %, respectively) [40]. Complete aneurysm occlusion was reported in 69.2 % at 6-month and 82.7 % at 18-month.…”
Section: Ia Coiling: Limits and Additional Techniques (Balloon-assistmentioning
confidence: 98%